The value of serum tau protein for the diagnosis of intracranial injury in minor head trauma - Kavalci, Cemil; Pekdemir, Murat; Durukan, Polat; Ilhan, Necip; Yidiz, Mustafa; Serhatlioglu, Selami; Seckin, Dilara (W B Saunders Co-Elsevier Inc, 2007)
Objective: Tau protein localizes in the axons of neuron cells, and it is released secondarily from the central nervous system because of hypoxia and trauma. In the present study, it was aimed to investigate the value of serum tau protein levels in diagnosing intracranial pathologies in minor head trauma. Methods: Patients were categorized into 2 groups: those without intracranial lesions in head CTs (group 1) and those with lesions in head CTs (group 2). Serum tau protein levels were determined. Results: Group 1 (n = 55) median serum tau protein level was 16.29 pg/mL (2.12-215.97 pg/mL) and group 2 (n = 33) median serum tau protein level was 18.39 pg/mL (2.19-714.47 pg/mL). Statistical analysis revealed no significant difference between the 2 groups for tau protein values, sex, age, mechanism of trauma, and Glasgow Coma Scale score. Conclusion: It is suggested that serum tau protein has limited value in minor head trauma. (C) 2007 Elsevier Inc. All rights reserved.
Keywords: Brain-Injury; Computed-Tomography; Damage; Mild; Emergency; Localization; Management; Markers; Map2